2001
DOI: 10.1093/humrep/16.5.1012
|View full text |Cite
|
Sign up to set email alerts
|

Regional differences in semen quality in Europe

Abstract: Recent reports have indicated a decrease in semen quality of men in some countries, and suggested regional differences. A study was undertaken of semen samples from 1082 fertile men from four European cities (Copenhagen, Denmark; Paris, France; Edinburgh, Scotland; and Turku, Finland). Semen analysis was standardized, inter-laboratory differences in assessment of sperm concentration were evaluated, and morphology assessment centralized. Lowest sperm concentrations and total counts were detected for Danish men,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

20
267
2
9

Year Published

2005
2005
2016
2016

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 423 publications
(298 citation statements)
references
References 34 publications
20
267
2
9
Order By: Relevance
“…Spatial heterogeneity has previously been observed in France in limited samples (Auger & Jouannet 1997), as well as in Europe (Jorgensen et al 2001) or in USA (Swan et al 2003), but little is known about the causal factors. The present study aims to analyze spatial patterns in France between 1989 and2005, using the same sample in which the global trends were calculated, in order to generate possible consistent hypotheses.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…Spatial heterogeneity has previously been observed in France in limited samples (Auger & Jouannet 1997), as well as in Europe (Jorgensen et al 2001) or in USA (Swan et al 2003), but little is known about the causal factors. The present study aims to analyze spatial patterns in France between 1989 and2005, using the same sample in which the global trends were calculated, in order to generate possible consistent hypotheses.…”
Section: Introductionmentioning
confidence: 98%
“…Temporal trends in human semen quality have been discussed for a long time, partly due to spatial heterogeneity (Jorgensen et al 2001) and methodological issues (Fisch 2008).…”
Section: Introductionmentioning
confidence: 99%
“…incidence of cryptorchidism, hypospadias and testicular cancer and semen quality) (8,9,10,11,12); we questioned whether population-level changes in testosterone levels would also be apparent in Finnish men and therefore not specific to men from Denmark and New England.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, both cryptorchidism and hypospadias were at least twice as common in Denmark than in Finland [8,9,10]. We also studied whether the differences in semen quality were true in well-controlled joint studies and found that semen quality of both fertile men and young men from the general population were worse in Denmark than in Finland [11,12]. Furthermore, the adverse changes in the incidence of most of these disorders took place in Denmark within a few decades [8,13].…”
Section: Case Study: Association Between Cryptorchidism and Dioxins Amentioning
confidence: 99%